The Effect of Emotional Intelligence and Workload on Employee Work Productivity at Pt Astra International Tbk – Daihatsu Sales Operation in Sleman - Mahadewi Kurnia Putri; Dwi Utami Puterisari (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study examines the effects of workload and emotional intelligence on employee productivity at PT Astra International Tbk - Daihatsu Sales Operation. A quantitative approach with saturation sampling yielded 57 respondents. Multiple linear regression analysis using IBM SPSS revealed that workload has a positive and significant impact on productivity, while emotional intelligence shows a positive but statistically insignificant effect. The simultaneous F-test confirms that both variables jointly exert a significant influence on productivity. These findings underscore the need for organizations to balance effective workload management and emotional competence to achieve optimal employee performance.